Molecular Aspects of DNA Splicing System - Yuhani, Yusof; Wen, Li Lim; T. Elizabeth, Goode; Nor Haniza, Sarmin; Fong, Wan Heng; Mohd Firdaus, Abdul Wahab (2015)
The pioneer model of deoxyribonucleic acid (DNA) splicing system in a framework of Formal Language Theory was introduced by Head that led to the existence of other models of splicing system, namely Paun, Pixton and Yusof-Goode. These entire models are inspired by the molecular biological process of DNA splicing. Hence, this paper focuses on the translucent DNA splicing process, particularly on the generated language. Starting with some preliminaries in a limit graph, this paper also provides the experimental design with the predicted and actual result.